2004
DOI: 10.1016/j.fuel.2003.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of a substitution fuel made of cardboard and polyethylene: influence of the mix characteristics—experimental approach

Abstract: This article presents an experimental study of the combustion of substitution fuels elaborated from compressed mixes of cardboard and polyethylene (PE). These components are representative of two classical classes of waste materials: materials derived from wood and plastics. The combustion of these fuels has been experimentally characterized in terms of combustion rate, and quantity of PolyAromatic Hydrocarbons (PAH) pollutants emitted. The temperature levels reached within the fuel sample are also reported an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 12 publications
(13 reference statements)
2
27
0
Order By: Relevance
“…These results support the conclusion of an earlier study (Salvador et al, 2004) in which negligible effect of LDPE on PAH emissions was observed in compressed mixtures of cardboard and LDPE until LDPE comprised more than 10% of the mass of the mixture. The study also supports the conclusion reached by Wrobel and Reinhardt (2003) that LDPE does not add additional toxic compounds to burning wood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results support the conclusion of an earlier study (Salvador et al, 2004) in which negligible effect of LDPE on PAH emissions was observed in compressed mixtures of cardboard and LDPE until LDPE comprised more than 10% of the mass of the mixture. The study also supports the conclusion reached by Wrobel and Reinhardt (2003) that LDPE does not add additional toxic compounds to burning wood.…”
Section: Discussionsupporting
confidence: 91%
“…Mutagenicity of organic extractives from particulate matter was also similar to that of residential wood smoke. Salvador et al (2004) examined the combustion rate and production of polycyclic aromatic hydrocarbons (PAHs) from cardboard and polyethylene mixtures compressed into fuel bricks of various densities and burned in a cone calorimeter. Mass percentage of LDPE in the mixtures was 0, 5, 10, 20, 33, 70, or 100.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly like on samples analysed with dynamic TG the H 3 PO 4 -treated samples 8 and 9 gave bigger residues at later stages of the process in comparison to the unmodified material although the temperature profile of these two processes is dramatically different [10]. In comparison to slow linear increase of temperature programmed for TGA experiments, the temperature increases much quicker when cone calorimeter is used [11,12]. The bigger residues are due to phosphorus incorporation into the material during Figures 1-3 it is evident, that all three types of relations are affected by the effect of thickness of specimens [13].…”
Section: Mass Loss Of Specimensmentioning
confidence: 83%
“…The main interest is probably to recover energy from materials, such as plastics, that cannot be incinerated by simple feeding of industrial furnaces. As reported previously [1], simple feeding of these materials without initial compaction generates two problems: handling is 419 a more detailed presentation. It was observed that combustion occurs in two different phases.…”
Section: Introductionmentioning
confidence: 96%
“…As the temperature of the solid increases, cardboard drying will occur, converting the adsorbed water into water vapor. When heated to 250 • C for cardboard and 450 • C for PE [1], devolatilization occurs. This will progressively convert cardboard and PE into gases, called volatile matter (VM), and leave a carbon solid residue, called char in the case of cardboard.…”
Section: Introductionmentioning
confidence: 99%